2019
DOI: 10.5858/arpa.2019-0298-cp
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Diagnosis of Reparative Changes and Malignancy: Performance in the College of American Pathologists Pap Education and Proficiency Testing Programs

Abstract: Context.— Repair is a challenging diagnosis and a significant source of false-positive (FP) interpretations in cervical cytology. No large-scale study of performance of repair in the liquid-based era has been performed. Objective.— To evaluate the performance of repair in the College of American Pathologists Pap Education and Proficiency Testing (PT) programs. Design.— The FP rate for slides classified as repair was evaluated by preparation type, participant type (cytotechnologist, pathologist, or laboratory),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Reparatory cells can look dramatic with the background of blood, leucocytes, and fibrin, which can give the impression of tumor diathesis. The main differentials of repair are HSIL and cancer [4,5,[12][13][14]. Morphological features of repair (shown in Fig.…”
Section: Repairmentioning
confidence: 99%
“…Reparatory cells can look dramatic with the background of blood, leucocytes, and fibrin, which can give the impression of tumor diathesis. The main differentials of repair are HSIL and cancer [4,5,[12][13][14]. Morphological features of repair (shown in Fig.…”
Section: Repairmentioning
confidence: 99%
“…Notably, repair may actually enter the differential diagnosis for invasive squamous cell carcinoma given that marked reactive/reparative processes may contain large nuclei with prominent and sometimes irregular nucleoli, and mitoses can be seen. Several studies have shown repair to be a significant source of both false‐positive and false‐negative cytological diagnoses, with the most common misclassifications being HSIL/carcinoma, adenocarcinoma, and adenocarcinoma in situ 31–36 . Included among the diagnostic clues, reparative cells typically have pale chromatin and tend to form more cohesive and well‐ordered sheets, and typically do not present as single atypical cells as may be seen with squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%